2018
DOI: 10.1017/s1368980017004128
|View full text |Cite|
|
Sign up to set email alerts
|

The nutritional content of supermarket beverages: a cross-sectional analysis of New Zealand, Australia, Canada and the UK

Abstract: There is substantial difference between countries in the mean energy, serving size and proportion of products eligible for fiscal sugar taxation. Current self-regulatory approaches used in these countries may not be effective to reduce the availability, marketing and consumption of sugar-sweetened beverages and subsequent intake of free sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…As well as soft drinks contributing phosphoric acid and caffeine to the diet, which are associated with poorer bone health [51], emerging evidence from animal studies and a few small human studies suggests that both caloric and noncaloric sweeteners in soft drinks may negatively affect bone [52]. Individuals living in New Zealand have the highest intake of sugar of any OECD country [53], with 39.6% of 15–18-year-old and 27.8% 19–30-year-old women consuming more than three soft/energy drinks each week [19]. New Zealand beverages have also recently been reported to have greater sugar levels per 100 mL than comparable drinks in Australia, Canada, and the UK [53].…”
Section: Discussionmentioning
confidence: 99%
“…As well as soft drinks contributing phosphoric acid and caffeine to the diet, which are associated with poorer bone health [51], emerging evidence from animal studies and a few small human studies suggests that both caloric and noncaloric sweeteners in soft drinks may negatively affect bone [52]. Individuals living in New Zealand have the highest intake of sugar of any OECD country [53], with 39.6% of 15–18-year-old and 27.8% 19–30-year-old women consuming more than three soft/energy drinks each week [19]. New Zealand beverages have also recently been reported to have greater sugar levels per 100 mL than comparable drinks in Australia, Canada, and the UK [53].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of behavioural intention raises significant concerns regarding the likelihood that SSB consumers will change their behaviour on their own volition. Past research has demonstrated that the sugar content and serving size of SSBs in countries with industry regulation exceed WHO recommendations ( Chepulis et al, 2018 ). In these countries, the onus falls on individuals to regulate the quantity and serving size of sugar they consume from SSBs.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of countries have implemented national taxes on SSBs, for instance, Fiji, Spain, Mexico, France, Tonga, Belgium, Saudi Arabia ( Thow et al, 2018 ), other countries such as New Zealand still rely on industry self-regulation. However, research shows self-regulation is not working: the sugar content and serving size of SSBs in countries adopting self-regulation exceed World Health Organisation (WHO) recommendations and New Zealand had the highest sugar content and availability of SSBs in the countries examined ( Chepulis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chepulis et al's paper (1) nevertheless shows that in New Zealand, almost one in two beverages (non-dairy) available in the supermarket do not contain (current author's underlining) any added sugar. We also know that:…”
Section: Closing Commentsmentioning
confidence: 99%